Konsep Investasi Pasar Modal dan Saham Syariah di Indonesia - St Samsuduha; Andi Herawati (Al-Tafaqquh: Journal of Islamic Law, 2023)
It is important to study the concept of investment in the capital market and sharia stocks to provide an understanding to investors. Indonesia has a capital market that is developing and continues to grow, thus encouraging the importance of implementing the Islamic capital market and sharia investment system, so that the practice system and its benefits can provide long-term benefits. Based on the results of the analysis, it was concluded that; (1) Investment is one of the muamalah that must be carried out in Islam based on sharia principles to avoid unfair practices so that it must comply with the principles of halal, blessing added value and the type of investment made must be realistic; (2) The Islamic capital market is an important means of facilitating the investment needs of Muslims in Indonesia. So far, investment space in the capital market tends to be considered legalized gambling, so this practice can trigger the interest of the Muslim generation to develop their capital potential in the investment sector; and (3) Islamic shares are included in the category of ordinary shares which have special characteristics such as a very strict control system such as a guarantee of business halalness that must be owned by shareholders. The sharia stock system must comply with principles that do not conflict with sharia values.